LEARNERS MOTIVATION OF PPA TUNAS KASIH ID0811 AND NON-PPA STUDENTS AT SDN 02 MAKALE UTARA - Enas Tavia Santopar; Sefrin S. Tangkearung; Iindarda S. Panggalo (Teaching English as a Foreign Language Overseas Journal, 2023)
This research was conducted based on the phenomenon at SDN 02 Makale Utara which showed a diversity of learning motivation between Non-PPA students and Child Development Center (PPA) students. This study aims to determine the difference in learning motivation between Non-PPA students and Child Development Center (PPA) students. The benefits of this research enrich the study of the learning motivation of Non-PPA students and Child Development Center (PPA) students in the world of Education. This type of research is comparative research. The study population was students of SDN 02 Makale Utara class IV, V, VI, and as a sample was the total number of 6 classes, then only 3 classes were taken with 10 children each class consisted of 5 Non-PPA students AND 5 PPA students classes IV, V and VI. Samples were taken by purposive sampling technique. Data collection methods and tools using learning motivation scales. The data analysis technique used is percentage descriptive analysis. The results showed a difference in learning motivation between Non-PPA students and Child Development Center (PPA) students. The percentage difference in learning motivation of Non-PPA students with PPA students based on indicators shows that the percentage value of PPA students is higher than Non-PPA students. Thus, there is a significant difference in learning motivation between Non-PPA students and Child Development Center (PPA) students, namely higher learning motivation of Child Development Center (PPA) students compared to Non-PPA students